Impact of CNTs' treatment, length and weight fraction on ordinary concrete mechanical properties - Mohamed O. Mohsen (17115667) (2020)
This study investigates the effect of the treatment, length and weight fraction parameters of multi-wall carbon nanotubes (MWCNT) on the mechanical properties of concrete. Mixes with various CNTs’ amounts ranging between 0.03 and 0.5 wt% were prepared using treated and untreated short and long CNTs. The flexural, compressive, and tensile strengths of the concrete composites were determined after 28, 56 and 90 days of curing. After that, the microstructures of the samples were investigated using a scanning electron microscope (SEM). The results were then analyzed using statistical t-tests to evaluate the significance of adding CNTs to concrete. The results showed that 0.03% long-treated CNTs increased compressive, flexural, and tensile strengths of ordinary concrete by 23, 29 and 20%, respectively. CNTs’ weight fraction and treatment parameters showed a noticeable effect on concrete strength. Concrete batches with 0.03 and 0.08% treated CNTs and 0.08% non-treated CNTs’ showed a relatively higher strength gain. Statistical t-tests confirmed that incorporating 0.03% long-treated CNTs into concrete had significantly improved compressive, flexural and tensile strengths. The analysis also showed that using fewer CNTs’ amounts of 0.03 and 0.08 wt% yielded higher strength results irrespective of the nanofilament treatment. Other Information Published in: Construction and Building Materials License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.conbuildmat.2020.120698